Oleuropein reduces the oxidative effects of tobacco smoke in rats’ liver and kidney - Kocamuftuoglu, Gonca Ozan; Kisacam, Mehmet Ali; Tektemur, Nalan Kaya; Yilmaz, Osman Fatih; Ozan, Ibrahim Enver; Ozan, Sema Temizer; Bircan, Filiz Sezen (Springer Science and Business Media Deutschland GmbH, 2022)
Tobacco smoke contains free radicals, which can potentiate the initiation and promotion of oxidative damage. Nitric oxide (NO) is easily converted into nitric oxide radicals found in tobacco smoke. Nitric oxide synthase and arginase, which might participate in oxidative stress, are two rival enzymes using the same substrate. Oleuropein (OLE) is the main phenolic compound found in olive leaves and has important antioxidant properties. In this study, potential protective effects of OLE on tobacco, smoke-exposed rats were evaluated. Eighteen male Sprague Dawley rats were divided into 3 groups: Control, Tobacco smoke, Tobacco smoke + OLE. The rats in tobacco smoke and tobacco smoke + OLE were exposed to tobacco smoke in a glass chamber for 1 h every other day for 12 weeks. Tobacco smoke + OLE were received 10 mg/kg OLE for the last 4 weeks by oral gavage. After 12 weeks, rats were decapitated; kidney and liver tissues were taken. Malondialdehyde (MDA), glutathione (GSH), NO levels together with catalase (CAT) and arginase activity were measured. MDA levels increased in the liver and kidney, while CAT activity and GSH levels decreased in tobacco smoke group. OLE administration decreased MDA levels while increasing CAT activity and GSH levels. NO levels increased in the liver following tobacco smoke, yet, OLE did not change NO significantly. Furthermore, kidney NO levels increased following tobacco smoke and OLE decreased this level. Tobacco smoke did not change kidney arginase levels while OLE decreased this activity. Our results showed that OLE could be beneficial in reducing the negative impact of tobacco smoke on both the liver and kidney. © 2022, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.
Keywords: Arginase; MDA; Oleuropein; Tobacco smoke